Measurement and Analysis of Tourism Website User Experience Using Usability Techniques - Rika Perdana Sari; Silvana Rasio Henim (Journal of Applied Engineering and Technological Science (JAETS), 2022)
A tourist destination is a geographical area within one or more administrative areas in which there are tourist attractions, public facilities, tourism facilities, accessibility, and communities that are interrelated and complement the realization of tourism. A website is a form of communication media that can provide certain information, which can be accessed by many people anytime and anywhere. The Regional Government (pemda) of Pekanbaru City has provided tourism information services in the form of tourist destinations and tourism activities on the website. Based on the results of preliminary observations made on the tourism website of the Pekanbaru City government, it was found that the tourism information provided was not up to date, and there were still many tourist objects in Pekanbaru that had not been published, so the information delivery process was not optimal and ineffective. The effectiveness of using the website must pay attention to usability of its use. Usability is a quality level of a system that is easy to learn, easy to use, and encourages users to use the system as a tool in completing tasks. Usability can be measured based on the quality of the user experience when interacting with the system operated by the user himself. Usability measurement on this tourism website is carried out using the System Usability Scale (SUS) measurement tool. Based on the measurement results using SUS, a score of 65.87 was obtained, where 10 of the statement items were declared valid and reliable. The score obtained shows that in terms of user satisfaction, it is stated to be included in the Marginal High category, predicate D with the adjective range Ok. This shows that the user's subjective assessment illustrates that the Pekanbaru City government's tourism website is less effective, efficient, and satisfying for users.